Implementasi DVR pada Saluran Penyulang Pujon dengan Kompensasi Tegangan Dip - Arief Trisno Eko Suryo; Wijono Wijono; Bambang Siswojo (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2020)
This paper discusses the DVR of on Pujon line with voltage Sag/Dip compensation. The voltage Dip is often the result of Single line-to-ground fault. The voltage Dip makes tripping and damage the load equipment a problem that must be addressed. DVR implementation is used to complement the voltage Dip. The ANN control method was proposed to regulate DVR performance in compensating the voltage Dip. Simulated results demonstrated with the implementation of a DVR in the Pujon replay line capable of compensating the voltage of the Single line-to-ground fault from a voltage drop that was originally 0536 PU and can be repaired by 0968 PU.